2018
DOI: 10.1177/0269215518757052
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Internet-based exercise compared with supervised group exercise in people with type 2 diabetes: a randomized controlled study

Abstract: In type 2 diabetes, supervised group-based and Internet-based exercise can improve equally glycaemic control, waist circumference, and quality of life, and both are better than simply counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 33 publications
2
46
1
Order By: Relevance
“…Looking at the cardiometabolic blood markers, WE had no effect on lipids and FBG. This is in contrast to a previous study which demonstrated positive effects of WE on FBG and TC [44]. However, the participants were adults with type 2 diabetes, which would explain the beneficial effects of the interventions given that exercise is more effective for improving metabolic outcomes in those with initially higher values [45].…”
Section: Discussioncontrasting
confidence: 73%
“…Looking at the cardiometabolic blood markers, WE had no effect on lipids and FBG. This is in contrast to a previous study which demonstrated positive effects of WE on FBG and TC [44]. However, the participants were adults with type 2 diabetes, which would explain the beneficial effects of the interventions given that exercise is more effective for improving metabolic outcomes in those with initially higher values [45].…”
Section: Discussioncontrasting
confidence: 73%
“…BMI was measured in four of the studies, while body fat percentage (BFP) and BW were measured in three studies. For the three studies where data were presented for both an IG and a CG (Akinci et al 2018;Thompson et al 2014;Wijsman et al 2013), there were significant decreases in WC in favor of the intervention within two of the studies. Specifically, in the study by Akinci et al, the IG decreased WC by a more than 5 cm compared to the CG (P \ 0.05) in the absence of effect on BMI.…”
Section: Discussionmentioning
confidence: 95%
“…The nature of digital exercise intervention varied widely between the five included studies. Akinci et al (2018) randomized participants to an IG and a CG. The CG received a brochure with information about health and exercise while the IG performed three exercise sessions for eight weeks, where each session lasted 50-60 min.…”
Section: Intervention Specificsmentioning
confidence: 99%
See 2 more Smart Citations